2012
DOI: 10.1016/j.bbr.2011.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor assessment of the unilateral 6-hydroxydopamine mouse model of Parkinson's disease

Abstract: Parkinson’s disease (PD), the second most common neurodegenerative disorder, is characterized by marked impairments in motor function caused by the progressive loss of dopaminergic neurons in the substantia nigra pars compacta (SNc). Animal models of PD have traditionally been based on toxins, such as 6-hydroxydopamine (6-OHDA) and 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP), that selectively lesion dopaminergic neurons. Motor impairments from 6-OHDA lesions of SNc neurons are well characterized in rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(90 citation statements)
references
References 80 publications
5
79
2
1
Order By: Relevance
“…The adhesive label is placed on each forepaw using a forcep and the time to remove the label is recorded. We found that 6-hyrdoxydopamine-treated mice will remove the label from the unaffected limb prior to removing the label on the affected limb 19 . This test battery is easy to implement in aging studies using chronic treatments but it is also easy to use in pharmacological studies.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…The adhesive label is placed on each forepaw using a forcep and the time to remove the label is recorded. We found that 6-hyrdoxydopamine-treated mice will remove the label from the unaffected limb prior to removing the label on the affected limb 19 . This test battery is easy to implement in aging studies using chronic treatments but it is also easy to use in pharmacological studies.…”
Section: Discussionmentioning
confidence: 79%
“…We have found alterations in sensorimotor function using these tests in multiple genetic and toxin mouse models of Parkinson's disease including parkin knockout, parkin Q311X, Pitx3-aphakia, alpha-synuclein overexpressing, and unilateral 6-hydroxydopamine mice 14,[16][17][18][19] . Here we show data collected from mice overexpressing human wildtype alpha-synuclein under the Thy1 promoter (Thy1-aSyn) and Pitx3-aphakia mice 18,20 .…”
Section: Representative Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gait analysis was done manually by measuring stride length (Glajch et al, 2012). Bottom of the fore limbs of rats were painted with kids paint and then they were allowed to walk on horizontal passage directed towards their cage.…”
Section: Neurobehavioral Analysismentioning
confidence: 99%
“…The use of either the left, right or both forelimbs for initial contact with the wall or floor of the cylinder was recorded. The percentage use of the limb contralateral to the lesion (contra) was expressed as a percentage of the contralateral limb on the total number of touches on the cylinder wall (Glajch et al, 2012).…”
Section: Limb-use Asymmetry Testmentioning
confidence: 99%